The use ultrasound guided for refilling intrathecal baclofene pump in complicated clinical cases: A practical approach. (November 2018) - Caruso, P.; Mazzon, G.; Sarra, V.M.; Tacconi, L.; Manganotti, P.
Highlights: Muscular spasticity due to neurological disorders is a heavy cause of severe pain and disability for many patients. Intrathecal baclofen therapy (ITB) is used as an important long term treatment to reduce spasticity. The ultrasound examination may identify the access port of ITB to avoid multiple needle punctures, infections, radiation exposition. Abstract: Muscular spasticity due to neurological disorders is a heavy cause of severe pain and disability for many patients, compromising the independence and quality life. Baclofene is a good tool to guarantee patients independence and pain control. Anyway in chronic therapy oral treatment become unsatisfactory. In all these cases, intrathecal baclofen therapy (ITB), after sub fascial implantation of intrathecal pumps is used as an important long term treatment to reduce spasticity. After pump implantation the drug reservoir must be refilled periodically in order to maintain the reduction of spasticity and avoid the symptoms and signs of withdrawal. ITB refilling, which involves the insertion of a needle through the skin until the access port of the pump, is often hard, mainly due to the layer of abdominal fat, spasticity, suboptimal pump positioning, pump rotation or inversion, and scar formation over the implantation site. To avoid the difficulties of ITB refilling radiography or other invasive supportive examinations are sometimes needed. We reported here our experience and we suggest a simple method to use the ultrasound in refilling with particular attention to some cases with complications after implantation with a difficult approach in refilling. We used the ultrasound examination to identify the access port of her pump so as to avoid multiple needle punctures and infections and radiation exposition. Ultrasound-guided technique may facilitate ITB refill in technically challenging cases. With ultrasound ITB was easily detectable and was quite simple to identify the exact point of needle injection. In the last years different new applications for ultrasounds are emerging. In our opinion the use of Doppler ultrasounds in the study of muscles and nerves represent an emerging tool for the physician's neurological rehabilitation.